Preparation method of antioxidant reverse osmosis membrane

By using antioxidants and crosslinking agents in the reverse osmosis membrane, combined with plasma treatment, ultraviolet curing and CVD deposition of silica, the problem of traditional reverse osmosis membranes being susceptible to oxidant erosion is solved, significantly extending the service life of the membrane and improving performance stability.

CN119524625APending Publication Date: 2025-02-28SUZHOU JIUXIN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411665478.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional reverse osmosis membranes are susceptible to erosion by oxidants during long-term use, resulting in oxidation and degradation of membrane materials, reducing mechanical strength and separation performance, and shortening service life.

Method used

Antioxidants such as BHT and antioxidant 1010 are used to combine the crosslinking agents glutaraldehyde and diisocyanate to deposit silica by plasma treatment, ultraviolet curing and CVD to enhance the antioxidant properties of the film.

Benefits of technology

Effectively delay the oxidation and degradation process of membrane materials, extend the service life of the membrane, improve mechanical strength and separation performance, and ensure that the membrane remains stable in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144474040000141
    Figure BDA0005144474040000141
  • Figure BDA0005144474040000151
    Figure BDA0005144474040000151
  • Figure HDA0005144474050000011
    Figure HDA0005144474050000011
Patent Text Reader

Abstract

The invention relates to the technical field of reverse osmosis membrane preparation, and discloses an anti-oxidation reverse osmosis membrane preparation method, which comprises the following specific steps: S1, material preparation: selecting polyamide PA or polyvinylidene fluoride PVDF as a membrane material, selecting BHT2, 6-butylated hydroxytoluene or an antioxidant 1010 as an antioxidant, selecting N-methyl pyrrolidone NMP or dimethylformamide DMF as a solvent, and preparing a reverse osmosis membrane; the cross-linking agent is selected from glutaraldehyde or diisocyanate; s2, preparing a membrane solution, namely dissolving polyamide or polyvinylidene fluoride in an NMP (N-methylpyrrolidone) or DMF (dimethylformamide) solvent, stirring until polyamide or polyvinylidene fluoride is completely dissolved, adding an antioxidant and a cross-linking agent, and continuously stirring uniformly; s3, forming a film; s4, forming a film by a phase inversion method; s5, curing and post-processing; s6, surface modification; and S7, performance testing. By adding the antioxidant, the oxidative degradation process of the membrane material is effectively delayed, the service life of the membrane is prolonged, and the oxidation resistance of the membrane is further enhanced through plasma treatment, ultraviolet curing and CVD deposition of silicon dioxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of reverse osmosis membrane preparation, in particular to a method for preparing an oxidation-resistant reverse osmosis membrane. Background Art

[0002] As a highly efficient separation technology, reverse osmosis membrane technology is widely used in seawater desalination, drinking water purification, industrial wastewater treatment and food processing. The main function of reverse osmosis membrane is to remove impurities such as dissolved salts, organic matter, bacteria and viruses in water through a semi-permeable membrane to obtain pure water.

[0003] Traditional reverse osmosis membranes are usually made of polymer materials such as polyamide (PA) or polyvinylidene fluoride (PVDF), which are easily corroded by oxidants (such as chlorine) during long-term use, leading to oxidative degradation of the membrane material. Oxidative degradation not only reduces the mechanical strength and separation performance of the membrane, but also shortens the service life of the membrane, increases replacement frequency and maintenance costs. Summary of the invention

[0004] In view of the deficiencies of the prior art, the present invention provides a method for preparing an oxidation-resistant reverse osmosis membrane, which solves the problem that the traditional reverse osmosis membrane is easily corroded by oxidants (such as chlorine) during long-term use, resulting in oxidative degradation of the membrane material.

[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: a method for preparing an oxidation-resistant reverse osmosis membrane, comprising the following specific steps:

[0006] S1: Material preparation, membrane material is polyamide PA or polyvinylidene fluoride PVDF, antioxidant is BHT2,6-di-tert-butyl-p-cresol or antioxidant 1010, solvent is N-methylpyrrolidone NMP or dimethylformamide DMF, cross-linking agent is glutaraldehyde or diisocyanate;

[0007] S2: preparing a membrane solution, dissolving polyamide or polyvinylidene fluoride in N-methylpyrrolidone (NMP) or dimethylformamide (DMF) solvent and stirring until completely dissolved, then adding an antioxidant and a cross-linking agent and continuing to stir evenly;

[0008] S3: Film formation: the mixed solution is evenly coated on a glass plate by coating or doctor blade coating, using an automatic coating machine with a coating speed set at 5-10 mm / s;

[0009] S4: film formation by phase inversion method, the substrate coated with the film solution is quickly immersed in deionized water to make the polymer solution phase separate;

[0010] S5: curing and post-treatment, curing the formed film in hot air at 80-100°C for 1-2 hours, and washing in running water for 30 minutes to remove residual solvent and unreacted chemicals;

[0011] S6: surface modification, using a plasma treatment device to treat the membrane surface with plasma, and then curing it in a UV curing device;

[0012] S7: Performance test: the anti-oxidation performance of the prepared reverse osmosis membrane is tested using an oxidation stress method, and the water permeability and retention rate of the membrane are tested.

[0013] Preferably, in the step S1, the weight percentage of polyamide PA is 2-5wt%, the weight percentage of polyvinylidene fluoride PVDF is 10-20wt%, the weight percentage of BHT2,6-di-tert-butyl-p-cresol is 0.1-0.5wt%, the weight percentage of antioxidant 1010 is 0.1-0.3wt%, the weight percentage of N-methylpyrrolidone NMP is 70-85wt%, the weight percentage of dimethylformamide DMF is 70-85wt%, the weight percentage of glutaraldehyde is 0.5-2wt%, and the weight percentage of diisocyanate is 0.5-2wt%.

[0014] Preferably, in the step S3, the coating thickness is controlled between 100-200 μm, in the step S4, the temperature of the deionized water is controlled between 20-25°C, the relative humidity is controlled between 60% and 70%, and the immersion time is 5-10 minutes, and in the step S6, the power of the plasma treatment instrument is set to 50-100 W, the treatment time is 1-5 minutes, and the UV intensity is 10-20 mW / cm 2 , the treatment time is 5-10 minutes, in the S7 step, the oxidant concentration is 0.1-0.5wt%, the test time is 24-48 hours, the water permeability refers to the amount of water passing through the membrane per unit time, and the retention rate refers to the percentage of solute removed.

[0015] Preferably, when the antioxidant and the cross-linking agent are added in step S1, a wetting agent Tween 80 and a stabilizer PEG are added, the weight percentage of the wetting agent Tween 80 is 0.1-0.3wt%, and the weight percentage of the stabilizer PEG is 0.5-1.5wt%.

[0016] Preferably, in the step S1, ultrasonic treatment or filtration is performed to remove tiny particles and bubbles in the solution, the frequency of the ultrasonic treatment is 40 kHz, the treatment time is 20 minutes, and the filtration selects a 0.45 μm filter membrane.

[0017] Preferably, in the step S5, freeze drying is finally performed, and the freeze drying needs to be dried at -50°C for 2-3 hours.

[0018] Preferably, in the step S6, silicon dioxide is deposited on the surface of the film by chemical vapor deposition (CVD) method, the deposition temperature is 100-150° C., and the deposition time is 30-60 minutes.

[0019] Preferably, in the step S7, a long-term oxidation stability test is performed to simulate the change in membrane performance under actual use environment, and the oxidation stability test includes testing in chlorinated water with a chlorine concentration of 1-5 ppm and a test time of 7-14 days.

[0020] The present invention provides a method for preparing an oxidation-resistant reverse osmosis membrane.

[0021] 1. The present invention effectively delays the oxidative degradation process of the membrane material and prolongs the service life of the membrane by adding an antioxidant. The anti-oxidation property of the membrane is further enhanced by plasma treatment, ultraviolet light curing and CVD deposition of silicon dioxide, so that it remains stable in harsh environments.

[0022] 2. The present invention forms a stable network structure through the use of cross-linking agents such as glutaraldehyde and diisocyanate through cross-linking reaction, thereby improving the mechanical strength and durability of the membrane. The curing and freeze-drying treatment steps ensure that the membrane does not shrink or deform during the drying process, thereby maintaining the integrity and stability of the membrane.

[0023] 3. The present invention ensures the uniformity of the membrane by controlling the membrane thickness between 100-200 μm and the coating speed between 5-10 mm / s, thereby achieving high water permeability and high retention rate. The phase inversion method ensures that the membrane forms a uniform pore structure, thereby improving the separation performance of the membrane.

[0024] 4. The present invention increases the hydrophilicity of the membrane surface, reduces the adsorption of pollutants, and improves the anti-pollution performance of the membrane through surface modification treatment such as plasma treatment and ultraviolet light curing treatment.

[0025] 5. The present invention uses a combination of multiple materials such as PA and PVDF to make the membrane have comprehensive performance and is suitable for different water treatment environments, including highly corrosive and high-temperature environments. It also simulates long-term testing in actual use environments to ensure the stability of the membrane's performance under complex conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart of a method for preparing an oxidation-resistant reverse osmosis membrane. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Please see attached Figure 1 The present invention provides a method for preparing an oxidation-resistant reverse osmosis membrane, comprising the following specific steps:

[0029] S1: Material preparation, membrane material is polyamide PA or polyvinylidene fluoride PVDF, antioxidant is BHT2,6-di-tert-butyl-p-cresol or antioxidant 1010, solvent is N-methylpyrrolidone NMP or dimethylformamide DMF, cross-linking agent is glutaraldehyde or diisocyanate;

[0030] S2: preparing a membrane solution, dissolving polyamide or polyvinylidene fluoride in N-methylpyrrolidone (NMP) or dimethylformamide (DMF) solvent and stirring until completely dissolved, then adding an antioxidant and a cross-linking agent and continuing to stir evenly;

[0031] Ensure that the membrane material is completely dissolved, which is conducive to forming a uniform membrane solution and providing uniform membrane performance. Adding antioxidants and cross-linking agents can ensure that various additives are evenly distributed in the membrane solution, thereby improving the membrane's antioxidant properties and stability.

[0032] S3: Film formation: the mixed solution is evenly coated on a glass plate by coating or doctor blade coating, using an automatic coating machine with a coating speed set at 5-10 mm / s;

[0033] The use of automatic coating machines can improve the accuracy and controllability of the film-forming process and ensure the consistency and uniformity of the film;

[0034] S4: film formation by phase inversion method, the substrate coated with the film solution is quickly immersed in deionized water to make the polymer solution phase separate;

[0035] The phase inversion method can form a uniform pore structure, improve the separation performance and stability of the membrane, and accurately control the conditions of the phase inversion process, which helps to obtain the ideal membrane structure and performance;

[0036] S5: curing and post-treatment, curing the formed film in hot air at 80-100°C for 1-2 hours, and washing in running water for 30 minutes to remove residual solvent and unreacted chemicals;

[0037] Thermal curing can enhance the mechanical strength and stability of the membrane, and cleaning can remove residual substances and prevent the membrane from degrading during use;

[0038] S6: surface modification, using a plasma treatment device to treat the membrane surface with plasma, and then curing it in a UV curing device;

[0039] Plasma treatment can introduce functional groups on the membrane surface, improve the hydrophilicity and anti-pollution properties of the membrane, and UV curing can form a protective layer on the membrane surface, improving the membrane's oxidation resistance and mechanical properties;

[0040] S7: Performance test: the anti-oxidation performance of the prepared reverse osmosis membrane is tested using an oxidation stress method, and the water permeability and retention rate of the membrane are tested.

[0041] The antioxidant performance test can evaluate the stability of the membrane in an oxidative environment to ensure its long-term performance. The water permeability and retention rate tests can evaluate the separation performance of the membrane to ensure its effectiveness in practical applications.

[0042] In step S1, the weight percentage of polyamide PA is 2-5wt%, the weight percentage of polyvinylidene fluoride PVDF is 10-20wt%, the weight percentage of BHT2,6-di-tert-butyl-p-cresol is 0.1-0.5wt%, the weight percentage of antioxidant 1010 is 0.1-0.3wt%, the weight percentage of N-methylpyrrolidone NMP is 70-85wt%, the weight percentage of dimethylformamide DMF is 70-85wt%, the weight percentage of glutaraldehyde is 0.5-2wt%, and the weight percentage of diisocyanate is 0.5-2wt%;

[0043] Polyamide (PA): As a matrix material, it provides good mechanical strength and chemical stability.

[0044] PA has good membrane forming properties and is suitable for use as a reverse osmosis membrane with high rejection rate and water permeability.

[0045] Polyvinylidene fluoride (PVDF): As a matrix material, it provides excellent chemical resistance and thermal stability.

[0046] The corrosion resistance and thermal stability of PVDF make it suitable for more demanding working environments and enhance the service life of the membrane.

[0047] BHT (2,6-di-tert-butyl-p-cresol): acts as an antioxidant to prevent oxidative degradation of polymer materials.

[0048] BHT can effectively delay the aging process of membrane materials and improve the durability and antioxidant properties of the membrane.

[0049] Antioxidant 1010: As an antioxidant, it inhibits oxidation reactions and protects film materials.

[0050] Antioxidant 1010 has highly effective antioxidant properties and can significantly improve the service life and stability of the membrane.

[0051] N-Methylpyrrolidone (NMP): As a solvent, it is used to dissolve polymer materials to form a uniform solution.

[0052] NMP has good dissolving power and can evenly dissolve the membrane material, ensuring uniformity and quality during the film forming process.

[0053] Dimethylformamide (DMF): As a solvent, it is used to dissolve polymer materials to form a uniform solution.

[0054] DMF has excellent solubility and volatility, which helps to form a uniform and dense membrane structure.

[0055] Glutaraldehyde: As a cross-linking agent, it is used to improve the mechanical strength and chemical stability of the membrane.

[0056] Glutaraldehyde can undergo cross-linking reactions with the functional groups in the membrane material, thus enhancing the chemical resistance and mechanical properties of the membrane.

[0057] Diisocyanate: As a cross-linking agent, it enhances the cross-linking degree of the membrane material and improves its stability.

[0058] Diisocyanates form a more stable network structure through cross-linking reaction, improving the durability and oxidation resistance of the film

[0059] In step S3, the coating thickness is controlled between 100-200 μm. In step S4, the temperature of deionized water is controlled between 20-25°C, the relative humidity is controlled between 60% and 70%, and the immersion time is 5-10 minutes. In step S6, the power of the plasma treatment instrument is set to 50-100 W, the treatment time is 1-5 minutes, and the UV intensity is 10-20 mW / cm 2 , the treatment time is 5-10 minutes, in step S7, the oxidant concentration is 0.1-0.5wt%, the test time is 24-48 hours, the water permeability refers to the amount of water passing through the membrane per unit time, and the retention rate refers to the percentage of solute removed.

[0060] Plasma treatment can improve the activity and hydrophilicity of the membrane surface.

[0061] Plasma treatment can introduce functional groups on the membrane surface, enhancing the membrane's anti-fouling properties and water flux.

[0062] Ultraviolet light is used to enhance the cross-linking degree and stability of the membrane surface.

[0063] UV curing can form a protective layer on the film surface, improving the film's oxidation resistance and mechanical properties.

[0064] When adding the antioxidant and the cross-linking agent in step S1, a wetting agent Tween 80 and a stabilizer PEG are added. The weight percentage of the wetting agent Tween 80 is 0.1-0.3wt%, and the weight percentage of the stabilizer PEG is 0.5-1.5wt%.

[0065] In step S1, ultrasonic treatment or filtration is performed to remove tiny particles and bubbles in the solution. The frequency of ultrasonic treatment is 40 kHz, the treatment time is 20 minutes, and the filtration is performed using a 0.45 μm filter membrane.

[0066] Eliminate particles and bubbles in the solution, prevent defects on the membrane surface, and ensure the uniformity and integrity of the membrane.

[0067] In step S5, freeze drying is finally performed, and the freeze drying process needs to be dried at -50°C for 2-3 hours;

[0068] Freeze drying prevents the membrane from shrinking or deforming during the drying process, maintaining the integrity and performance of the membrane.

[0069] In step S6, silicon dioxide is deposited on the surface of the film by chemical vapor deposition (CVD) method, the deposition temperature is 100-150° C., and the deposition time is 30-60 minutes.

[0070] A dense protective layer of silicon dioxide is deposited on the surface of the membrane by CVD method.

[0071] The protective layer deposited by CVD can effectively prevent the oxidation and degradation of the membrane, and improve the service life and stability of the membrane

[0072] In step S7, a long-term oxidation stability test is performed to simulate the membrane performance changes under the actual use environment. The oxidation stability test includes testing in chlorinated water with a chlorine concentration of 1-5ppm and a test time of 7-14 days;

[0073] Long-term oxidation stability testing can evaluate the durability of the membrane in the actual use environment and ensure its stable performance under complex conditions.

[0074] The following is an introduction in conjunction with specific embodiments:

[0075] Embodiment 1:

[0076] Material preparation

[0077] Membrane material:

[0078] Polyamide (PA): 4wt%

[0079] Antioxidants:

[0080] BHT (2,6-di-tert-butyl-p-cresol): 0.3wt%

[0081] Solvent:

[0082] N-Methylpyrrolidone (NMP): 80 wt%

[0083] Crosslinking agent:

[0084] Glutaraldehyde: 1.5wt%

[0085] Other additives:

[0086] Wetting agent (Tween 80): 0.2wt%

[0087] Stabilizer (PEG): 1wt%

[0088] Preparation process

[0089] Prepare membrane solution:

[0090] Polyamide (PA) was dissolved in NMP and stirred until completely dissolved to a concentration of 4 wt%.

[0091] BHT (0.3 wt%), glutaraldehyde (1.5 wt%), Tween 80 (0.2 wt%) and PEG (1 wt%) were added and the mixture was stirred until uniform.

[0092] The fine particles and bubbles in the solution were removed by ultrasonic treatment (40 kHz, 20 minutes).

[0093] Film formation:

[0094] The solution was evenly coated on a glass plate by blade coating, and the coating thickness was controlled at 150 μm.

[0095] An automatic coating machine was used and the coating speed was set to 7 mm / s.

[0096] Phase inversion film formation:

[0097] The substrate coated with the membrane solution was quickly immersed in deionized water (temperature 22° C.) and kept for 10 minutes to allow the polymer solution to phase separate and form a dense reverse osmosis membrane.

[0098] Curing and post-processing:

[0099] The formed film was cured in hot air at 90° C. for 1 hour.

[0100] Rinse in running water for 30 minutes to remove residual solvent and unreacted chemicals.

[0101] The product was freeze-dried at -50°C for 2 hours.

[0102] Surface modification:

[0103] The membrane surface was plasma treated using a plasma treatment instrument, with the power set to 75 W and the treatment time being 3 minutes.

[0104] Performance Test:

[0105] For the antioxidant performance test, the oxidant concentration was 0.3 wt % and the test time was 36 hours.

[0106] Water permeability: 80L / m 2 ·h, the interception rate is 98%.

[0107] Embodiment 2:

[0108] Material preparation

[0109] Membrane material:

[0110] Polyvinylidene fluoride (PVDF): 15wt%

[0111] Antioxidants:

[0112] Antioxidant 1010: 0.2wt%

[0113] Solvent:

[0114] Dimethylformamide (DMF): 75 wt%

[0115] Crosslinking agent:

[0116] Diisocyanate: 1wt%

[0117] Other additives:

[0118] Stabilizer (PEG): 1wt%

[0119] Preparation process

[0120] Prepare membrane solution:

[0121] Dissolve polyvinylidene fluoride (PVDF) in DMF and stir until completely dissolved to a concentration of 15 wt%.

[0122] Antioxidant 1010 (0.2 wt %), diisocyanate (1 wt %) and PEG (1 wt %) were added and stirred until uniform.

[0123] The fine particles and bubbles in the solution were removed by ultrasonic treatment (40 kHz, 20 minutes).

[0124] Film formation:

[0125] The solution was uniformly coated on a glass plate by coating, and the coating thickness was controlled at 150 μm.

[0126] An automatic coating machine was used and the coating speed was set to 6 mm / s.

[0127] Phase inversion film formation:

[0128] The substrate coated with the membrane solution was quickly immersed in deionized water (temperature 24° C.) and kept for 7 minutes to allow the polymer solution to phase separate and form a dense reverse osmosis membrane.

[0129] Curing and post-processing:

[0130] The formed film was cured in hot air at 85° C. for 1.5 hours.

[0131] Rinse in running water for 30 minutes to remove residual solvent and unreacted chemicals.

[0132] The product was freeze-dried at -50°C for 3 hours.

[0133] Surface modification:

[0134] The curing process was carried out in a UV curing device with a UV light intensity of 15mW / cm 2 , the processing time is 8 minutes.

[0135] Performance Test:

[0136] For the antioxidant performance test, the oxidant concentration was 0.4 wt % and the test time was 48 hours.

[0137] Water permeability: 70L / m 2 h, the interception rate is 97%.

[0138] Example 3: Material preparation

[0139] Membrane material:

[0140] Polyamide (PA): 3wt%

[0141] Polyvinylidene fluoride (PVDF): 12wt%

[0142] Antioxidants:

[0143] BHT (2,6-di-tert-butyl-p-cresol): 0.4wt%

[0144] Antioxidant 1010: 0.2wt%

[0145] Solvent:

[0146] N-Methylpyrrolidone (NMP): 80 wt%

[0147] Crosslinking agent:

[0148] Glutaraldehyde: 1wt%

[0149] Other additives:

[0150] Wetting agent (Tween 80): 0.3wt%

[0151] Preparation process

[0152] Prepare membrane solution:

[0153] Polyamide (PA) and polyvinylidene fluoride (PVDF) were mixed and dissolved in NMP and stirred until completely dissolved, with concentrations of 3 wt % and 12 wt %, respectively.

[0154] BHT (0.4 wt %), antioxidant 1010 (0.2 wt %), glutaraldehyde (1 wt %) and Tween 80 (0.3 wt %) were added and the mixture was stirred until uniform.

[0155] The fine particles and bubbles in the solution were removed by ultrasonic treatment (40 kHz, 20 minutes).

[0156] Film formation:

[0157] The solution was evenly coated on a glass plate by blade coating, and the coating thickness was controlled at 160 μm.

[0158] An automatic coating machine was used and the coating speed was set to 8 mm / s.

[0159] Phase inversion film formation:

[0160] The substrate coated with the membrane solution was quickly immersed in deionized water (temperature 23° C.) and kept for 8 minutes to allow the polymer solution to phase separate and form a dense reverse osmosis membrane.

[0161] Curing and post-processing:

[0162] The formed film was cured in hot air at 95° C. for 1 hour.

[0163] Rinse in running water for 30 minutes to remove residual solvent and unreacted chemicals.

[0164] The product was freeze-dried at -50°C for 2 hours.

[0165] Surface modification:

[0166] Silicon dioxide was deposited on the film surface by chemical vapor deposition (CVD) at a temperature of 130° C. for 45 minutes.

[0167] Performance Test:

[0168] For the antioxidant performance test, the oxidant concentration was 0.5 wt % and the test time was 24 hours.

[0169] Water permeability: 75L / m2 h, the retention rate is 96%.

[0170] Table 1: Properties of Anti-Oxidation Reverse Osmosis Membranes in Different Embodiments

[0171]

[0172]

[0173] Among them, the table fields are explained as follows:

[0174] Water permeability: Evaluates the water flux performance of the membrane.

[0175] Retention rate: evaluates the separation performance of the membrane.

[0176] Anti-fouling performance: Evaluate the membrane's anti-fouling ability during use.

[0177] Mechanical strength: Evaluate the tensile and compressive properties of the membrane.

[0178] Chemical resistance: Evaluates the stability of the membrane in different chemical environments.

[0179] Thermal stability: Evaluates the performance of the membrane in high temperature environments.

[0180] Service life: Evaluate the long-term performance of the membrane.

[0181] Applicable environment: Evaluate the applicability of the membrane in different water treatment environments.

[0182] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing an oxidation-resistant reverse osmosis membrane, characterized in that: The specific steps include: S1: Material preparation, membrane material is polyamide PA or polyvinylidene fluoride PVDF, antioxidant is BHT2,6-di-tert-butyl-p-cresol or antioxidant 1010, solvent is N-methylpyrrolidone NMP or dimethylformamide DMF, cross-linking agent is glutaraldehyde or diisocyanate; S2: preparing a membrane solution, dissolving polyamide or polyvinylidene fluoride in N-methylpyrrolidone (NMP) or dimethylformamide (DMF) solvent and stirring until completely dissolved, then adding an antioxidant and a cross-linking agent and continuing to stir evenly; S3: Film formation: the mixed solution is evenly coated on a glass plate by coating or doctor blade coating, using an automatic coating machine with a coating speed set at 5-10 mm / s; S4: film formation by phase inversion method, the substrate coated with the film solution is quickly immersed in deionized water to make the polymer solution phase separate; S5: curing and post-treatment, curing the formed film in hot air at 80-100°C for 1-2 hours, and washing in running water for 30 minutes to remove residual solvent and unreacted chemicals; S6: surface modification, using a plasma treatment device to treat the membrane surface with plasma, and then curing it in a UV curing device; S7: Performance test: the anti-oxidation performance of the prepared reverse osmosis membrane is tested using an oxidation stress method, and the water permeability and retention rate of the membrane are tested.

2. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: In the step S1, the weight percentage of polyamide PA is 2-5wt%, the weight percentage of polyvinylidene fluoride PVDF is 10-20wt%, the weight percentage of BHT2,6-di-tert-butyl-p-cresol is 0.1-0.5wt%, the weight percentage of antioxidant 1010 is 0.1-0.3wt%, the weight percentage of N-methylpyrrolidone NMP is 70-85wt%, the weight percentage of dimethylformamide DMF is 70-85wt%, the weight percentage of glutaraldehyde is 0.5-2wt%, and the weight percentage of diisocyanate is 0.5-2wt%.

3. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: In the step S3, the coating thickness is controlled between 100-200 μm, in the step S4, the temperature of the deionized water is controlled between 20-25° C., the relative humidity is controlled between 60% and 70%, and the immersion time is 5-10 minutes, in the step S6, the power of the plasma treatment instrument is set to 50-100 W, the treatment time is 1-5 minutes, and the ultraviolet light intensity is 10-20 mW / cm 2 , the treatment time is 5-10 minutes, in the S7 step, the oxidant concentration is 0.1-0.5wt%, the test time is 24-48 hours, the water permeability refers to the amount of water passing through the membrane per unit time, and the retention rate refers to the percentage of solute removed.

4. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: When adding the antioxidant and the cross-linking agent in step S1, a wetting agent Tween 80 and a stabilizer PEG are added. The weight percentage of the wetting agent Tween 80 is 0.1-0.3wt%, and the weight percentage of the stabilizer PEG is 0.5-1.5wt%.

5. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: In the step S1, ultrasonic treatment or filtration is performed to remove tiny particles and bubbles in the solution. The frequency of the ultrasonic treatment is 40 kHz, the treatment time is 20 minutes, and the filtration is performed using a 0.45 μm filter membrane.

6. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: In the step S5, freeze drying is finally performed, and the freeze drying needs to be dried at -50°C for 2-3 hours.

7. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: In the step S6, silicon dioxide is deposited on the surface of the film by chemical vapor deposition (CVD) method, the deposition temperature is 100-150° C., and the deposition time is 30-60 minutes.

8. The method for preparing an oxidation-resistant reverse osmosis membrane according to claim 1, characterized in that: In the step S7, a long-term oxidation stability test is performed to simulate the change in membrane performance under actual use environment. The oxidation stability test includes testing in chlorinated water with a chlorine concentration of 1-5 ppm and a test time of 7-14 days.